Full Implementation of the Genetic Code by Tryptophanyl-tRNA Synthetase Requires Intermodular Coupling - Li, Li (American Society for Biochemistry and Molecular Biology, 2013)
Tryptophanyl-tRNA Synthetase (TrpRS) Urzyme (fragments A and C), a 130-residue construct containing only secondary structures positioning the HIGH and KMSKS active site signatures and the specificity helix, accelerates tRNA(Trp) aminoacylation with ∼10-fold specificity toward tryptophan, relative to structurally related tyrosine. We proposed that including the 76-residue connecting peptide 1 insertion (Fragment B) might enhance tryptophan affinity and hence amino acid specificity, because that subdomain constrains the orientation of the specificity helix. We test that hypothesis by characterizing two new constructs: the catalytic domain (fragments A–C) and the Urzyme supplemented with the anticodon-binding domain (fragments A, C, and D). The three constructs, together with the full-length enzyme (fragments A–D), comprise a factorial experiment from which we deduce individual and combined contributions of the two modules to the steady-state kinetics parameters for tryptophan-dependent (32)PP(i) exchange, specificity for tryptophan versus tyrosine, and aminoacylation of tRNA(Trp). Factorial design directly measures the energetic coupling between the two more recent modules in the contemporary enzyme and demonstrates its functionality. Combining the TrpRS Urzyme individually in cis with each module affords an analysis of long term evolution of amino acid specificity and tRNA aminoacylation, both essential for expanding the genetic code. Either module significantly enhances tryptophan activation but unexpectedly eliminates amino acid specificity for tryptophan, relative to tyrosine, and significantly reduces tRNA aminoacylation. Exclusive dependence of both enhanced functionalities of full-length TrpRS on interdomain coupling energies between the two new modules argues that independent recruitment of connecting peptide 1 and the anticodon-binding domain during evolutionary development of Urzymes would have entailed significant losses of fitness.